The Effectiveness of the Cooperative Integrated Reading and Composition (CIRC) Learning Model on the Indonesian Language Reading Comprehension Skills of Fourth Grade Elementary School Students - Wahyuni, Ida; Efendi, Ujang; Siregar, Rabiyatul Adawiyah; Diana, Siska Mega; Destini , Frida (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
The purpose of this study was to determine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model on students' reading comprehension skills. This study used a quasi-experimental method with a nonequivalent control group design. The study population was all students at the elementary school where the study was conducted, with a sample of 58 students selected using purposive sampling. Data collection was carried out through tests and non-tests. Data analysis used prerequisite tests, including the homogeneity test, the Shapiro-Wilk normality test, and the Levene test. To test the effectiveness of the learning model, parametric tests were used: the independent sample t-test and simple linear regression with the help of IBM SPSS version 27. The results of the study indicate that the application of the CIRC learning model has a positive influence on students' reading comprehension skills and produces a significant difference in reading comprehension skills between the experimental class and the control class. This model is effective because it involves integrated reading, writing, and discussion activities, thus helping students understand the content of the reading better. Learning with this model also encourages students to be active in finding important information and drawing conclusions from the reading. These findings indicate that the CIRC model can be an alternative learning method to improve reading comprehension skills in Indonesian subjects